Kompozyty żywicy epoksydowej zmodyfikowanymi bentonitami dla potrzeb przemysłu lotniczego - Oleksy, M.; Oliwa, R.; Heneczkowski, M.; Mossety-Leszczak, B.; Galina, H.; Budzik, G. (Polimery, 2012)
Composites were prepared from commercial bisphenol A based epoxy resin Epidian 6 (EP6) filled with bentonite Specjal (BS) modified with quaternary ammonium salts (QAS) (Fig. 2). The paper describes the influence of the modified bentonite content (1.5—4.5 wt. %) on the application properties of the as-prepared nanocomposites and laminates made from them, reinforced with glass fibre fabrics. The mechanical and flame resistant properties of the nanocomposites were investigated in view of their possible application in aircraft structural components (Table 1, 2; Figs. 3, 4). Nanocomposites consisting of EP6 resin matrix and BS modified with QAS aswell as the laminates prepared from them displayed markedly improved flame resistance compared to the unfilled resin.